PENGGUNAAN PASIR PANTAI RUTAH DAN KERIKIL PANTAI SEPA TERHADAP KUAT TEKAN BETON - Pieter L. Frans; Indah A. Tuaputty; Abraham Tuanakotta, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Concrete consists of mixing fine aggregate, coarse aggregate, by adding cement adhesive and water as auxiliary materials for chemical reactions during the hardening process. The Amahai sub-district area is in a coastal area so many people use Rutah Beach sand and Sepa Beach gravel for economic reasons and are easy to obtain. This research aims to compare and determine the compressive strength value of concrete produced from concrete using Rutah beach sand as a substitute for fine aggregate and using coarse aggregate in the form of Sepa Beach gravel with normal concrete compressive strength. The research was carried out on cylindrical test objects with a diameter of 15cm and a height of 30cm. The tests carried out were testing the compressive strength of concrete at the ages of 7, 14 and 28 days, with 3 test object samples taken at each age. The test results at the age of 7 days mean the compressive strength of the concrete is 16.14 MPa. At the age of 14 days the average compressive strength of the concrete is 20.57 MPa and at the age of 28 years the average compressive strength of the concrete is 22.55 MPa.